1996
DOI: 10.1007/bf00232468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jasmonates and exogenous polysaccharides on production of alkannin pigments in suspension cultures of Alkanna tinctoria

Abstract: The conditions for the efficient production of alkannin pigments by a suspension culture of Alkanna tinctoria were established. Pectin, polygalacturonic acid sodium salt and galactan increased the pigment production but not as much as agar did. A marked increase in the pigment content in cells and medium of suspension cultures after treatment with methyl jasmonate was observed. It was shown, applying a two-layer culture method, that mineral and olive oils intensified the pigment secretion from cells to the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…( Beerhues and Berger, 1995 ). A marked increase in the alkannin pigment content in cells and medium of suspension cultures of Alkanna tinctoria after treatment with MJ was observed ( Urbanek et al, 1996 ). The addition of 0.5 μM MJ provoked a twofold to threefold increase in anthocyanin production over that of the control in cell cultures of Vaccinium pahalae ( Fang et al, 1999 ).…”
Section: Elicitation Of Secondary Metabolites Using Jasmonatesmentioning
confidence: 99%
“…( Beerhues and Berger, 1995 ). A marked increase in the alkannin pigment content in cells and medium of suspension cultures of Alkanna tinctoria after treatment with MJ was observed ( Urbanek et al, 1996 ). The addition of 0.5 μM MJ provoked a twofold to threefold increase in anthocyanin production over that of the control in cell cultures of Vaccinium pahalae ( Fang et al, 1999 ).…”
Section: Elicitation Of Secondary Metabolites Using Jasmonatesmentioning
confidence: 99%
“…The type of plant growth regulators and explant may be fundamental factors for production of A/S derivates (Urbanek et al 1996) which optimized suspension cultures of A. tinctoria for efficient production of alkannin. B5 medium supplemented with 2 mg/l 2-4, D, 0.5 mg/l BAP and 7 g/l agar was reported to be suitable for callus formation of A. tinctoria using root.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial production of A/S and its derivatives were first produced by callus culture of Lithospermum erythrorhizon (Tabata et al 1974). It is also reported that A/S and it derivatives were produced using tissue culture techniques for different species, e.g., callus culture of Alkanna tinctoria (Urbanek et al 1996), root and suspension culture of Lithospermum canescens (Tatsumi et al 2016), suspension culture of Echium italicum L. (Zare et al 2010), callus culture and suspension culture of Arnebia hispidissima (Singh and Sharma 2014), callus culture of Onosma bulbotrichom (Bagheri et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported increased production of alkanin/shikonin and their derivatives (A/S) in cell cultures of Boragenaceous plants (e.g., Lithospermum erythrorhizon, Alkanna tinctoria, and Arnebia euchroma) after applying exogenous jasmonate (Gaisser and Heide 1996;Urbanek et al 1996;Bychkova et al 1993). Alkanin/shikonin are naphtoquinone compounds with a broad spectrum of biological activities, such as wound healing, anti-inflammatory, and anticancer (Kheiri et al 2017;Kourounakis et al 2002;Andújar et al 2013).…”
Section: Mechanisms By Which Amf Symbiosis Promotes Secondary Metabol...mentioning
confidence: 99%